Rare Mycobacterial Infections in Kidney Transplant Recipients – Case Reports - Chilaka Rajesh; Utkarash Mishra; Athul Thomas; Jeethu Joseph Eapen; Sabina Yusuf; Elenjickal Elias John; Anna T. Valson; Suceena Alexander; Vinoi George David; Joy Sarojini Michael; Santosh Varughese (Indian Journal of Transplantation)
To study the clinical profile and outcomes of rare mycobacterial infections such as nontuberculous mycobacteria (NTM) and Mycobacterium leprae kidney transplant recipients. This is a retrospective analysis of clinical outcomes of the uncommon infections in renal allograft recipients over 22 years during 2000–2022 from a tertiary care center in southern India; the clinical data were obtained from electronic medical records of nephrology and clinical microbiology departments. Institutional review board approved this study vide minute number 13641 dated 02.12.2020. A total of 1970 patients underwent renal transplantation at our institute, from January 1, 2000, to December 31, 2022. During this period, five patients were diagnosed with mycobacterial infections, three of whom had NTM infections and two with Mycobacterium leprae infections. The patients were all diagnosed by isolating organism in blood and/or pus cultures. All patients were similarly managed initially with a reduction of immunosuppressive drugs and appropriate antibiotics as per protocol. At present, there is no standard serodiagnostic test available to reliably detect patients with rare infections. Initial cultures may yield negative results due to slow growth and inconsistent colony appearance. Our research revealed that the majority of patients had negative sputum cultures and negative Gram stains. Therefore, it is essential to maintain a high level of suspicion and conduct thorough investigations in postrenal transplant recipients to achieve early diagnosis, administer appropriate treatment, and prevent disease spread.